A Note on Gold Movements in the Present International Monetary System - Lutz, F. (Review of Economic Studies, 1937)
Journal Article A Note on Gold Movements in the Present International Monetary System Get access F. Lutz F. Lutz Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 1, October 1937, Pages 66–71, https://doi.org/10.2307/2967581 Published: 01 October 1937